Optimal Replenishment policy for Items with Three-parameter Weibull distribution Deterioration, Stock-level dependent Demand and partial backlogging - SANNI, Smaila S.; CHIGBU, Polycarp E. (Yugoslav Journal of Operations Research; Vol 28 No 1 (2018), 2017)
Our focus in this paper is on determining an optimal replenishment policy for items with three-parameter Weibull distribution deterioration and inventory-level dependent demand. We developed and analyzed the model under the assumption of partial backlogging. The three-parameter Weibull hazard rate captures the impact of already deteriorated items that are received into the inventory, as well as those items that may start deteriorating in future. The inventory-level demand reﬂects a real market demand for product whose sales is enhanced by stock on display. We study a case base examples to gain some quantitative insight into the proposed model and we perform sensitivity analysis to draw some managerial implications. Keywords: Inventory Model, Stock-Dependent Demand, Dierential Equation, Optimal Policy, Hazard function.